Convergence and divergence issues in the regional growth pattern - Abdul Shukor Ariffin (Universiti Kebangsaan Malaysia, 1976)
The convergence and divergence issues have been keenly debated in relation to the growth process. A similar issue occurs with respect to the pattern of regional growth. Some opinions have suggested that the process of regional growth in a free market will lead to a convergence in regional income per capita. This would occur from three main sources. They are factor price equalisation, reallocation of resources within regions, and convergence of regional growth caused by a decline in the growth rate of developed region. However there are opinions which have pointed out that the convergence in regional growth process cannot occur even if the three factors mentioned are taken into account. One opinion has gone even further to suggest that factor movements between regions may even worsen the problems of regional economic imbalance. In other words the 'divergence' process in more predominant than that of the 'convergence' process.